USAHA BUDIDAYA DAN PENGOLAHAN ANEKA KULINER JAGUNG DI KECAMATAN KUMPEH KABUPATEN MUARO JAMBI - Edison; Dharia Renate (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract: There have been various efforts made by corn farmers in improving their competitiveness and the ability to market their corn. It turns out that by turning their cultivated corn into corn culinary, the selling value of corn has improved, but in terms of technical processing, the target audience has not been able to work on corn-based culinary products. The corn processing method is relatively simple, because they are familiar with such tools as cauldrons, blenders and so on. The implementation of service is useful so that: (a) the target audience gains expertise on how to treat good harvests, (b) understands good corn culinary processing, (c) is skilled at making corn culinary. Likewise, service is intended to obtain benefits such as: (a) to improve post-harvest knowledge of corn in order to get the best product, (b) seek activities in the agro-industrial sector so that it can help get "value added", and (c) distribute science and technology that needs to be understood and used. The service activities will be divided into 4 components, namely counseling, field visits, practice and field consultation. The service was carried out in Mekar Sari Village, Kumpeh Jambi District in early 2021. Participants who took part in the service included corn farmers, PKK Corn Farmers Group women, Mekar Sari Village, Kumpeh District, Muaro Jambi Regency. Taking into account the situation and conditions such as the available place and time, the target audience who participated in the PPM was 50 participants. From the results of the activity, encouraging results were obtained, where the enthusiasm of participants in participating in the activity increased by 30%, there was an increase in understanding of the corn culinary processing process by 35%, and the desire to take part in further activities also increased. Abstrak: Sudah berbagai upaya dilakukan petani jagung dalam memperbaiki kemampuan saing serta kemampuan memasarkan jagung mereka. Ternyata dengan menjadikan jagung hasil budidaya mereka menjadi kuliner jagung, nilai jual jagung jadi membaik, tapi pada teknis pengolahannya khalayak sasaran belum mampu mengerjakan produk kuliner berbasis jagung. Metoda pengolahan jagung relatif sederhana, karena mereka telah mengenal alat tersebut seperti kuali, blender dan sebagainya. Pelaksanaan pengabdian berguna supaya: (a) khalayak sasaran mendapatkan keahlian mengenai cara perlakuan panen yang baik, (b) memahami cara pengolahan kuliner jagung yang baik, (c) terampil membuat kuliner jagung. Demikian pula pengabdian diperuntukan dalam mendapatkan kegunaan seperti: (a) untuk perbaikan pengetahuan pasca panen jagung dalam rangka mendapatkan produk terbaik, (b) mencari kegiatan disektor agroindustri jadi bisa membantu mendapatkan “value added”, serta (c) mendistribusikan IPTEKS yang perlu dipahami serta digunakan. Pada kegiatan pengabdian, akan dipilah jadi 4 komponen yakni penyuluhan, kunjungan lapang, praktek dan konsultasi lapang. Pengabdian dilakukan di Desa Mekar Sari Kecamatan Kumpeh Jambi awal Tahun 2021. Peserta yang mengikuti pengabdian seperti petani jagung, ibu-ibu PKK Kelompok Tani Jagung Desa Mekar Sari, Kecamatan Kumpeh, Kabupaten Muaro Jambi. Dengan pertimbangan situasi dan kondisi seperti tempat serta waktu yang tersedia, khalayak sasaran yang berpartisipasi pada PPM berjumlah 50 peserta. Dari hasil kegiatan diperoleh hasil yang menggembirakan, dimana antusias peserta mengikuti kegiatan meningkat 30%, terjadi peningkatan pemahaman mengenai proses pengolahan kuliner jagung sebesar 35%, dan keinginan untuk mengikuti kegiatan lebih lanjut juga meningkat.